THE ADVANTAGES OF SOCIAL SOLIDARITY TO BE AN IDEAL LEADER ACCORDING TO IBNU KHALDUN - Kasmuri Selamat; Irma Handayani; Akhyar Hanif (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The ideal leader is an expectation for every society in the world. Leadership is a relationship between the influence of the leader and the one being led. Leadership also functions to execute power to invite, influence, guide, mobilize and build other people to do something to achieve certain goals. To implement, Islam provides normative and philosophical bases on the principles of leadership. These principles include deliberation, fairness, gentleness, freedom of thought, synergy in building togetherness. The principles taught by Islam are in line with the thoughts of one of the Islamic philosophers, Ibn Khaldun. Furthermore, he emphasized that the social solidarity factor is crucial to become an ideal leader.